Evaluation of promising algal strains for sustainable exploitation coupled with CO2 fixation. Issue 5 (3rd March 2016) - Singh, Shailendra Kumar; Rahman, Akhlaqur; Dixit, Kritika; Nath, Adi; Sundaram, Shanthy
ABSTRACT: The photosynthetic activity of three microalgae, Chlamydomonas reinhardtii, Chlorella AU1, Scenedesmus AU1, and six cyanobacteria, Spirulina platensis, Anabaena cylindrica, Oscillatoria AU1, Nostoc muscurum, Synechococcus AU1, Synechocystis sp. PCC6803, was investigated. Strains S. platensis, Scenedesmus AU1 sp. and Chlorella AU1 sp. showed the highest fluorescence quenching than other strains tested. Thus, these were selected for mitigation analysis in a designed tubular photobioreactor system at 0.06%, 6%, 12%, 18% and 24% concentrations. Spirulina showed maximum biomass productivity of 1.03 g L −1  d −1 with the highest fixation rate of 0.678 g   L −1  d −1 at 6% concentration. The maximum protein content (66.63%) was also achieved in Spirulina sp. at 6% concentration. Thus, Spirulina could be utilized as a source of protein supplement coupled with fixation. Maximum carbohydrate proportion (51.71%) was noted with Scenedesmus AU1 sp. at 12% . Scenedesmus AU1 sp. also accumulated the maximum lipid content (25.07%) at 6% concentration, which was further analysed for biodiesel production. The extracted Scenedesmus oil was mainly rich in short chain fatty acids (C-16 : 0, C-18:1, C-18:2, C-18:3) which is an ideal combination for efficient biodiesel. Thus, this is vital in helping to choose Scenedesmus as a biodiesel feedstock, coupled with fixation.